Pro Windows Small Business Server 2003 - Campbell, Tony (Apress : Imprint: Apress, 2006)
Microsofts Windows Small Business Server has taken the market by storm, offering a compelling solution for business with 50 or fewer employees. Pro Windows Small Business Server 2003 is a complete guide for intermediate-to-advanced administrators who have deployed the Small Business Server, gotten it working for their organizations, and want to take the product and its features to the next level. This book is your solid reference to SBS 2003, and you'll gain great insight to IT security. Inside this book, you'll find everything you need to know about managing SBS 2003 on a daily basis. Author Tony Campbell walks through all the aspects of installing and running the products in the suite. Specific topics include Windows Server 2003 R2, Windows SharePoint Services, Exchange Server 2003, Microsoft Office Outlook 2003, Microsoft Shared Fax Service, Routing and Remote Access, as well as coverage of the Premium Edition, and even a chapter on troubleshooting. A requirements gathering and mapping exercise will teach you how to best plan a small businesss IT system.